Brokerstwo informacyjne w Polsce – przegląd publikacji - Walczak-Niewiadomska, Agata; Czapnik, Grzegorz; Gruszka, Zbigniew (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The article describes texts on information brokering, profession related to the occupation of LIS specialists. This issue has occurred in Polish general and professional literature in the mid 1990’s. Overview of the publications contains 128 works published in the Polish language, which consists of books, articles (both print and electronic), examples of thematic blogs and multimedia presentations. These sources relate only to issues of general information brokerage, excluding matters of business information and Competitive Intelligence.